2010
DOI: 10.1186/1471-2229-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of DNA methylation and Histone H4 acetylation during floral bud differentiation in azalea

Abstract: BackgroundThe ability to control the timing of flowering is a key strategy for planning production in ornamental species such as azalea, however it requires a thorough understanding of floral transition. Floral transition is achieved through a complex genetic network and regulated by multiple environmental and endogenous cues. Dynamic changes between chromatin states facilitating or inhibiting DNA transcription regulate the expression of floral induction pathways in response to environmental and developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…The present study shows in a monocot species that, in contrast with the DNA methylation increase in gametophytic development, microspore reprogramming to embryogenesis is associated with very low levels of global DNA methylation. Significant variations in global DNA methylation have been related to global changes of gene expression occurring during plant vegetative developmental processes [Meijón et al, 2010]. The present data reveal epigenetic modifications which accompany the reprogramming of the microspore towards a new developmental program and the first embryogenic divisions.…”
Section: Discussionmentioning
confidence: 79%
“…The present study shows in a monocot species that, in contrast with the DNA methylation increase in gametophytic development, microspore reprogramming to embryogenesis is associated with very low levels of global DNA methylation. Significant variations in global DNA methylation have been related to global changes of gene expression occurring during plant vegetative developmental processes [Meijón et al, 2010]. The present data reveal epigenetic modifications which accompany the reprogramming of the microspore towards a new developmental program and the first embryogenic divisions.…”
Section: Discussionmentioning
confidence: 79%
“…Sampling times for PGRs analysis were selected taking into account the previous results of methylation dynamics and morphological variations during floral transition observed in a previous work (Meijón et al 2010b). Quantification of PAs was performed on the samples in September (the period immediately after floral induction), October (in which cell reorganization seems to happen) and February (an advanced stage of flowering bud development), while the levels of CKs and GAs were analysed only in samples in September.…”
Section: Methodsmentioning
confidence: 99%
“…The switch to flowering involves integration and coordination of environmental perception (day length, light conditions and temperature) and endogenous factors such as developmental status and age. This coordination is decisive for reproductive success in plants, and its correlation with epigenetic mechanisms such as DNA methylation has been demonstrated in several species (Dennis and Peacock 2007, Farrona et al 2008), including azaleas (Meijón et al 2009b, 2010b). It has been shown that DNA methylation plays an essential role in the processes of cellular proliferation and differentiation, allowing cells to be reprogrammed in order to generate new differentiation pathways (Exner and Hennig 2008, Meijón et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most MIAs are built from the secoiridoid secologanin 3 and the indole-containing molecule tryptamine 2 (Figure 1a) [9]. Strictosidine synthase (STS) condenses these two molecules via a Pictet-Spengler condensation that forms strictosidine 4 , which is believed to ultimately succumb to either of two chemical fates [9,10]. If the plant is not under herbivore attack, strictosidine 4 is deglucosylated and rearranged into the over 3000 MIAs found in nature [10].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, if the plant is under herbivore attack, the strictosidine 4 pool (estimated to be approximately 10 mM in periwinkle leaf epidermal cells hormonally treated to mimic herbivore attack) can be directed to the nucleus for mass deglucosylation, leading to a reactive dialdehyde species capable of cross-linking proteins [10]. This mechanism has been dubbed the strictosidine nuclear “bomb” in reference to the “mustard oil bomb” mechanism of glucosinolate biosynthesis (see below) [10]. Importantly, many of the MIA metabolites themselves have also been implicated in plant defense strategies [11].…”
Section: Introductionmentioning
confidence: 99%